THE COMPARATIVE ANALYSIS OF UNIVERSITY EDUCATION IN UKRAINE AND THE NETHERLANDS IN THE CONTEXT OF THE BOLOGNA TREATIES - Zaiats, Liudmyla I. (Educological discourse, 2014)
The article highlightsuniversity systems of Ukraine and the Netherlands under the conditions of their integration into the European educational area. The authoranalyses the achievements of Ukrainian and Dutch higher education in the implementation of the Bologna agreement principles and determines prioritiesin terms of Ukrainian university education reforms. The author also expresses the ideas of the employment of Dutch university education reform experiencefor the Ukrainian higher education modernization.